Engineering exsolved catalysts for CO2 conversion - Ali, Swali A.; Safi, Manzoor; Merkouri, Loukia-Pantzechroula; Soodi, Sanaz; Iakovidis, Andreas; Duyar, Melis S.; Neagu, Dragos; Reina, Tomas Ramirez; Kousi, Kalliopi (Frontiers in Energy Research, 2023)
Innovating technologies to efficiently reduce carbon dioxide (CO2) emission or covert it into useful products has never been more crucial in light of the urgent need to transition to a net-zero economy by 2050. The design of efficient catalysts that can make the above a viable solution is of essence. Many noble metal catalysts already display high activity, but are usually expensive. Thus, alternative methods for their production are necessary to ensure more efficient use of noble metals. Exsolution has been shown to be an approach to produce strained nanoparticles, stable against agglomeration while displaying enhanced activity. Here we explore the effect of a low level of substitution of Ni into a Rh based A-site deficient titanate aiming to investigate the formation of more efficient, low loading noble metal catalysts. We find that with the addition of Ni in a Rh based titanate exsolution is increased by up to 4 times in terms of particle population which in turn results in up to 50% increase in its catalytic activity for CO2 conversion. We show that this design principle not only fulfils a major research need in the conversion of CO2 but also provides a step-change advancement in the design and synthesis of tandem catalysts by the formation of distinct catalytically active sites.